Age- and Urothelium-related Changes in Hydrogen Sulfide-induced Responses in Mouse Bladder - Fatma Aydinoglu; Tugba Toyran; Nuran Ogulener (Journal of Physiological Investigation)
The alterations in bladder function are associated with aging. Hydrogen sulfide (H2S) is a gaseous neurotransmitter that is synthesized in the urinary bladder and is suggested to regulate bladder smooth muscle tone. The effects of age and urothelium on the L-cysteine/H2S-induced relaxant responses were investigated in young (3–4 months) and aged (23–24 months) mice. The relaxant responses to endogenous H2S (L-cysteine) augmented in denuded urothelium bladder tissue in both age groups. However, the relaxant responses to exogenous H2S (sodium hydrogen sulfide: 1 μM - 3 mM) did not change by disruption of the urothelium. The contractile response to carbachol increased in intact bladder tissues of aged mice compared to young mice. On the other hand, contractile responses to carbachol decreased in the denuded bladder tissues of aged compared to young mice. In addition, cystathionine-β-synthase, cystathionine-γ-lyase (CSE), and 3 mercaptopyruvate sulfurtransferase (3-MST) enzymes which are responsible for H2S synthesis were intensively detected in the urothelium and vascular smooth muscle of bladder by immunohistochemistry. CSE and 3-MST were observed lesser in the smooth muscle of aged bladder tissue. These results suggest that relaxation to the L-cysteine/H2S pathway and contraction to carbachol of the bladder are affected by aging and urothelium. H2S- and urothelium-related molecular and biological changes may be responsible for bladder dysfunctions by aging. Understanding the mechanisms involved in chemical and mechanical signaling of the H2S pathway may provide important insights into the development of novel targets for the clinical management of age-related bladder dysfunctions in human such as overactive bladder, lower urinary tract symptoms, and other urological diseases. In this context, it is important to note that L-cysteine/H2S pathway may be recognized a new therapeutic target bladder disorders.